2022
DOI: 10.1007/s41109-022-00464-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex graph matching matched filters

Abstract: We consider the problem of detecting a noisy induced multiplex template network in a larger multiplex background network. Our approach, which extends the graph matching matched filter framework of Sussman et al. (IEEE Trans Pattern Anal Mach Intell 42(11):2887–2900, 2019) to the multiplex setting, utilizes a multiplex analogue of the classical graph matching problem to use the template as a matched filter for efficiently searching the background for candidate template matches. The effectiveness of our approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…We also found that BGM outperforms GM for any combination of network layers for both connectomes. These results highlight the advantages of combining BGM with a previously described extension of graph matching [30] when multiple edge types are available, as the highest accuracy on both datasets came from using both contralateral connections and multiple edge types.…”
Section: Extensionssupporting
confidence: 58%
See 4 more Smart Citations
“…We also found that BGM outperforms GM for any combination of network layers for both connectomes. These results highlight the advantages of combining BGM with a previously described extension of graph matching [30] when multiple edge types are available, as the highest accuracy on both datasets came from using both contralateral connections and multiple edge types.…”
Section: Extensionssupporting
confidence: 58%
“…For each combination of layers, BGM always showed an increase in mean matching accuracy over GM (p-values < 0.005 for all of these comparisons, two-sided Mann-Whitney U test). On both datasets, the best results came from using BGM (this work) in concert with the multiplex graph matching proposed in Pantazis et al [30].…”
Section: Extensionsmentioning
confidence: 94%
See 3 more Smart Citations